The Relation Between Voluntary Disclosure and Financial Reporting: Evidence from Synthetic Leases - ZECHMAN, SARAH L. C. (Journal of Accounting Research, 2010)
ABSTRACT I investigate how the use and voluntary disclosure of synthetic leases is affected by incentives to defer cash outflows and manage the financial statements by keeping debt off the balance sheet. I find that managers of cash‐constrained firms with incentives to defer cash payments are more likely to finance asset purchases with synthetic leases. The mandated reporting for synthetic leases allows managers to avoid disclosing the financial consequences of these transactions. Managers of firms with incentives to use off‐balance‐sheet financing do not provide transparent disclosure about their synthetic leases. However, managers of cash‐constrained firms, which are less likely to use synthetic leases for financial reporting reasons, do voluntarily disclose the existence and financial consequences of these contracts. Alternative tests around FIN 46 adoption corroborate these findings.